2010
DOI: 10.1038/cdd.2010.127
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic spine loss and neurodegeneration is rescued by Rab11 in models of Huntington's disease

Abstract: Huntington's disease (HD) is a fatal neurodegenerative disorder caused by expansion of a polyglutamine tract in the huntingtin protein (htt) that mediates formation of intracellular protein aggregates. In the brains of HD patients and HD transgenic mice, accumulation of protein aggregates has been causally linked to lesions in axo-dendritic and synaptic compartments. Here we show that dendritic spines -sites of synaptogenesis -are lost in the proximity of htt aggregates because of functional defects in local e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 48 publications
10
58
0
Order By: Relevance
“…It was previously shown that RAB11 is required for the fusion of autophagosomes with multivesicular bodies (MVBs). [44][45][46] These studies reported that depletion of RAB11 results in the decreased convergence of RAB11-decorated MVBs with LC3-labeled autophagosomes. Furthermore, this role of RAB11 may be affected by the toxic aggregates of the HTT/huntingtin protein during Huntington disease (HD), which can lead to neurodegeneration.…”
Section: The Golgi Gatekeepers: Rab1 and Rab11mentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that RAB11 is required for the fusion of autophagosomes with multivesicular bodies (MVBs). [44][45][46] These studies reported that depletion of RAB11 results in the decreased convergence of RAB11-decorated MVBs with LC3-labeled autophagosomes. Furthermore, this role of RAB11 may be affected by the toxic aggregates of the HTT/huntingtin protein during Huntington disease (HD), which can lead to neurodegeneration.…”
Section: The Golgi Gatekeepers: Rab1 and Rab11mentioning
confidence: 99%
“…112 Several studies showed that RAB11 dysfunction or loss of its activity underlies the cellular pathomechanism of HD [113][114][115] and in various HD models, RAB11 is able to rescue the neuronal loss. 46,116 Besides RAB11, RAB8 is also involved in HD and its mislocalization results in perturbation of post-Golgi trafficking to lysosomes 117 that may affect autophagic degradation. Dysregulation of the autophagic process is found in HD as well.…”
Section: Autophagic Rabs In Pathological Conditionsmentioning
confidence: 99%
“…Therefore, we used a Drosophila model of HD, in which flies pan-neuronally express a mutant HTT exon 1 fragment (HTT93Q) and exhibit a progressive loss of photoreceptor neurons (rhabdomeres) during their lifespan. [34][35][36][37][38] Treatment of adult HD flies with either mometasone or GRT10 markedly rescued mutant HTT-mediated neurodegeneration, although the extent of protection with GRT10 was slightly lower than with mometasone (Figures 3c and d). Moreover, treatment of the glucocorticoids during larval stages reduced neurodegeneration in newly emerged (day 0) HD flies (Figure 3e), suggesting that the transrepression arm of glucocorticoid signaling is neuroprotective both in adult HD flies and during development.…”
Section: Resultsmentioning
confidence: 99%
“…Mutant Htt expression disrupts both Rab8 and Rab11 activity by affecting normal localization of Rab8 on Golgi membranes (20) and by impairing guanine nucleotide exchange factor activity on Rab11, resulting in reduced recycling of cargo proteins (21). Expression of a constitutively active form of Rab11 in primary neurons from an HD mouse model ameliorates deficits in extracellular cysteine uptake by restoring cell surface levels of the glutamate transporter EAAC1 (22), and overexpression of Rab11 in a Drosophila model of HD rescues neurodegeneration and extends lifespan (23). Thus, it is possible that manipulating the activity and expression levels of HAP1, dynein, Rab8, and Rab11 might ameliorate at least some aspects of ciliary dysfunction in HD.…”
Section: How Does Mutant Htt Affect Cilia Function?mentioning
confidence: 99%